A Parallel AES of Faster Image Transfer Using Genetic Algorithm Key Generation - Patil, Suvarna; Thakare, AD (International Journal of Computer Sciences and Engineering, 2015)
Now exponentially increased the use of information exchange and the multimedia applications. Security is the essential criterion in cryptography for the transmission of data or message in the secured form in all the applications. For preserving the privacy of data onto different applications encryption is a crucial technique. Advanced Encryption Standard algorithm is used for encrypting the image. The genetic algorithm is an important method of solving the optimization problem. This paper is based on the genetic algorithm used for making the encryption key stronger. Using parallel AES algorithm the experimental results show that it improves the fastness of the AES algorithm and meet the security demand.